Egosentrisme Anak pada Perkembangan Kognitif Tahap Praoperasional - Yesi Novitasari; Danang Prastyo (PG-PAUD Trunojoyo, 2020)
Egocentric thinking is the inability of children to see the perspective of others in seeing problems and prioritizing their own perspectives. Egocentric many appear at an early age. Related to this, this research purpose to analyze the egocentrism of children in cognitive development, in the preoperational stage.This research is a descriptive study using a quantitative approach. The sample of this research was 30 children aged 4-6 years. The research sample was taken with a total sampling technique. The results of the analysis data showed that the children's egocentrism in cognitive development in the preoperational stage reached 76.33% with a very high category. Each aspect value are imaginative thinking amounted to 72.08%, egocentric language amounted to 82.92%, had a high I amounted to 74.58%, high curiosity amounted to 80.42%, and language development began rapidly amounted to 71, 67%.